SCHOOL LITERACY MOVEMENT ON READING LITERACY SKILLS IN ELEMENTARY SCHOOL STUDENTS - Andini, Regita Ayu; Nurhidayati, Nurhidayati; Anjarini, Titi (Jurnal Visipena, 2025)
This study aims to evaluate the effect of the School Literacy Movement (SLM) on the literacy skills of fifth-grade students, involving a sample of 15 participants. Literacy skills were assessed using the Minimum Competency Assessment (MCA) literacy scores. A quantitative experimental design was employed, utilizing a one-group pretest-posttest approach. Data were collected through interviews with homeroom teachers, followed by pretesting, the implementation of the literacy intervention, and posttesting. Data analysis using SPSS version 22 revealed that the normality test for both pretest and posttest scores yielded p-values of 0.230 and 0.570, respectively, indicating a normal distribution. The Levene’s test for homogeneity of variance produced a p-value of 0.178, confirming homogeneity across the group. The findings showed a 2% increase in students’ average MCA literacy scores after the implementation of the SLM, suggesting a measurable improvement in literacy skills. These results underscore the role of school-based literacy programs in enhancing students' literacy competencies and support the continued development and integration of literacy initiatives in primary education.